CH4 dissociation on the Pd/Cu(111) surface alloy: A DFT study - Akça Aykan (Open Physics, 2020)
The periodic four-layered model of the pure Cu(111) surface has been considered, and the effect of doping with palladium on CH4 dissociation has been investigated. The most stable adsorption geometries of CHx species (x = 1–4) and H atom on the PdCu(111) and pure Cu(111) surfaces have been obtained. Their computed adsorption energy results on the pure Cu(111) surface have been compared with the previously reported studies. Then, transition state geometries of CH4 dehydrogenation steps on both surfaces were calculated by the climbing image nudged elastic band method. Finally, the relative energy diagram for CH4 complete dehydrogenation has been represented. The results show that the PdCu(111) surface is more favorable than the Cu(111) surface in terms of the activation energies. The addition of Pd atoms to the Cu(111) surface significantly improves the catalytic activity. This knowledge can enable an efficient catalyst design at a lower cost using different strategies.